UPAYA KEMENTERIAN AGAMA DALAM MENCEGAH DAN MENANGANI KASUS KEKERASAN SEKSUAL DI PONDOK PESANTREN KABUPATEN SITUBONDO - Ainur Rosyidah (Pascasarjana Universitas Al-Qolam Malang, 2025)
The increasing number of cases of sexual violence in Islamic boarding schools is a cause for concern and fear for the people who send their children to boarding. Because this phenomenon has become a national issue, the role of the Ministry of Religion as supervisor of Islamic boarding schools must be responsive in resolving this case. Therefore, efforts must be made by the Ministry of Religion to prevent and handle cases of sexual violence in Islamic boarding schools in Situbondo Regency, considering that the impact on victims of sexual violence is very large, such as fear, depression and even suicide. Because victims are often afraid of being blamed by society, even if the report is not handled immediately. Because those who are reported have a high position and honor in the eyes of society. This research aims to analyze the efforts of the Situbondo Ministry of Religion in preventing and handling sexual violence in Islamic boarding schools in Situbondo Regency and then describe the challenges and strategies of the Situbondo Ministry of Religion in efforts to prevent and handle cases of sexual violence in Islamic boarding schools in Situbondo Regency. This research method uses qualitative descriptive methods, Field Research while the data collection techniques used are 3 ways, namely observation, interviews and documentation. Meanwhile, data analysis and management techniques use Miles and Huberman analysis, namely data reduction, data presentation, drawing conclusions or data verification. The findings from this research are the Ministry of Religion's efforts to prevent cases of sexual violence at the Situbondo Islamic Boarding School, namely developing rules and policies, conducting regular audits and a safe reporting system, then building cooperation with institutions and providing strict sanctions. Meanwhile, the Ministry of Religion's efforts to handle cases of sexual violence at the Situbondo Islamic Boarding School are by providing education and training to students and teachers by introducing the dangers and impacts of sexual violence.